The story of a shipwrecked sailor who drifted on a life raft for ten days without food or water, was proclaimed a national hero, kissed by beauty queens, made rich through publicity, and then spurned by the government and forgotten for all time - Garcia Marquez, Gabriel 1927-2014 (New York Vintage Books, 1989)
In 1955, Garcia Marquez was working for El Espectador, a newspaper in Bogota, when in February of that year eight crew members of the Caldas, a Colombian destroyer, were washed overboard and disappeared. Ten days later one of them turned up, barely alive, on a deserted beach in northern Colombia. This book, which originally appeared as a series of newspaper articles, is Garcia Marquez's account of that sailor's ordeal.
Translation of: Relato de un naufrago.
This translation originally published: New York : Knopf, 1986.
Translation of: Relato de un náufrago.
Keywords: Velasco, Luis Alejandro; Caldas (Ship).; Shipwreck survival; Shipwreck survival -- Caribbean Sea; Survival after airplane accidents, shipwrecks, etc; Sailors -- Colombia -- Biography; Survival at sea